Isomorfisme Institusional LPSK dalam Penegakan Hak Rehabilitasi Psikososial Korban Tindak Pidana di Indonesia - Mahari Is Subangun; Sudarsono Harjosoekarto (Jurnal HAM, 2023)
This study explains how isomorphism develops in the Indonesian Witness and Victim Protection Agency (Lembaga Perlindungan Saksi dan Korban-LPSK) and contributes to stronger coordination among institutions in administering psychological services for crime victims in Indonesia. This study employs an organizational sociology approach with an isomorphism perspective to determine the robustness of institutions' roles and relationships in providing psychosocial care to crime victims. Using the Soft Systems Methodology (SSM) in conjunction with Textual Network Analysis (TNA), this study discovered that coercive isomorphism in government organizations is the primary driving factor behind mimetic and normative isomorphism, whereas stereotyped isomorphism drives the private sector. Isomorphism emerges to give psychosocial services to victims of criminal crimes, namely as a result of reinforcement from Law Number 31 of 2014 on the Protection of Witnesses and Victims. This reinforcement prompted mimetic isomorphism in many forms of cooperation, and as a result, normatively, it is feasible to claim that LPSK has evolved into a professional institution in delivering psychological rights services to victims of criminal crimes. Furthermore, this study makes recommendations on the role of state institutions and cooperative institutions in satisfying the rights of crime victims in Indonesia, particularly psychosocial assistance.